Principal Leadership in Improving Teacher Performance at Karo State Islamic Senior High School - Geniza Aidilla Syuaira; Makmur Syukri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This study was conducted to explain how the principal affects the performance of teachers at MAN Karo, as well as the factors that support or hinder the leadership of the principal in improving the performance of teachers in the school. This study uses a qualitative descriptive method with case studies, which means that the researcher will collect in-depth information about how the principal's leadership affects the performance of teachers in the school. The subjects in this study are school principals and teachers at MAN Karo. To collect the data, researchers used observations, interviews, and document studies. The results of this study show that the leadership of the Principal at MAN Karo is quite good in fostering teacher performance. They provide motivation, supervision, and evaluation of teachers' performance well. On the other hand, the teacher's performance is also quite good in preparing learning plans, managing learning activities, and evaluating learning.